Enhancing the imaging quality and fabrication efficiency of bionic compound eyes using a sandwich structure. Issue 10 (7th June 2018) - Luo, Jiasai; Guo, Yongcai; Wang, Xin
Abstract: This paper puts forward a novel method for fabrication of sandwich-structured BCE using a detachable micro-hole array (MHA) prepared by 3D printing. Compared with most traditional methods, 3D printing enables effective implementation of direct micro-fabrication for curved BCE without the pattern transfer and substrate reshaping process. This 3D fabrication method allows rapid fabrication of the curved BCE and automatic assembly of the detachable MHA using a custom-built mold under negative pressure. The formation of a multi-focusing micro-lens array (MLA) was realized by adjusting the parameters of the curved detachable MHA. The imaging performance was effectively enhanced by the sandwich structure that consist of the multi-focusing MLA, the outer detachable MHA and the inner solidified MHA. This method is suitable for mass production due to its advantages as a time-saving, cost-effective and simple process. Optical design software was used to analyze the optical properties, and an imaging simulation was performed.